Cucurbit[6]uril‐Derived Sub‐4 nm Pores‐Dominated Hierarchical Porous Carbon for Supercapacitors: Operating Voltage Expansion and Pore Size Matching. Issue 39 (23rd August 2020) - Qiu, Daping; Li, Min; Kang, Cuihua; Wei, Jinying; Wang, Feng; Yang, Ru
Abstract: The intrinsic properties of carbon‐based material and the voltage window of electrolyte are the two key barriers to restrict the energy density of carbon‐based supercapacitors (SCs). Herein, a cucurbit[6]uril‐derived nitrogen‐doped hierarchical porous carbon (CBC x ) with unique pore structure characteristics is synthesized and successfully applied to construct SCs based on different electrolyte systems. Owing to narrow pore size distribution (0.5–4 nm), colossal ion‐accessible pore volume, prominent supermesopore volume, and reasonable heteroatom configuration, the CBC x ‐based SCs demonstrate excellent electrochemical performances with high operating voltages in two distinct systems. The optimal SCs can output a maximum energy/power density of 18 Wh kg −1 (11.1 Wh L −1 )/20 kW kg −1 (12.3 kW L −1 ) with an operating voltage of 1.2 V in potassium hydroxide aqueous electrolyte, as well as an ultralong cycle life of up to 50 000 cycles (0.046% decay per 100 cycles). Furthermore, the optimal SCs deliver an exceptionally high energy/power density of 95 Wh kg −1 (58.4 Wh L −1 )/70 kW kg −1 (43 kW L −1 ) with an ultrahigh operating voltage of 3.5 V in 1‐ethyl‐3‐methylimidazolium tetrafluoroborate electrolyte. This work opens up a new application field for cucurbit[6]uril and provides an alternative avenue for optimizing the performances of carbon‐based materials for SCs. Abstract : A cucurbit[6]uril‐derived sub‐4 nm pores‐dominated hierarchical porous carbon combining narrow pore size distribution (0.5–4 nm), colossal ion‐accessible pore volume, prominent supermesopore volume, and reasonable heteroatom configuration is synthesized, and successfully applied to assemble supercapacitors based on two distinct electrolyte systems.